Optical rhinometry in nasal provocation testing - Krzych-Fałta, Edyta; Sybilski, Adam; Wojas, Oksana; Samoliński, Bolesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Optical rhinometry (ORM) is a technique that allows for direct continuous measurement of changes in blood flow (optical density) in nasal vessels, at the same time analyzing changes per unit of time in the evaluated variable: intravascular blood flow and oxygen saturation. Aim : To assess the extent to which ORM can be used as an objective measure of nasal mucosal edema following a nasal allergen provocation test in a group of patients with allergic rhinitis versus healthy controls. Material and methods : The study group included 60 subjects: 30 patients diagnosed with an allergy to common environmental allergens (dust mites/grasses) and 30 healthy controls. The method used in the study was a nasal provocation test with an allergen, with a standard dose of a control solution and an allergen (5,000 SBU/ml) administered using a calibrated atomizer into both nostrils in room temperature. Results : The mean delay to the onset of nasal mucosal response as measured by ORM was 3.15 min and the level of light extinction returned to baseline after 28.15 min (change in optical density 0.431). These objective changes in optical density strongly correlated with subjective perception measured via a visual analog scale. Conclusions : Optical rhinometry is a valuable tool for nasal allergen provocation testing.